ART THERAPY FLASH MOB AS A MEANS OF REDUCING ANXIETY IN CHILDREN - Дацун, Олена (Proceedings of the National Aviation University. Series: Pedagogy, Psychology, 2025)
The article presents an analysis of art therapeutic flash mob as a form of psychological support and a means of reducing anxiety in children in conditions of full-scale invasion. The relevance of the study is due to the increase in the level of anxiety manifestations in childhood and the limited possibilities of using traditional verbal methods of psychological assistance in crisis situations. The purpose of the article is substantiation of the potential of an art therapy flash mob as an accessible and safe tool for emotional support for children using the example of the author’s flash mob "Thoughts about Mriya", dedicated to the image of the AN-225 "Mriya" aircraft, which emerged in the first days of the full-scale invasion. To solve the tasks set, the following were used research methods: analysis of scientific literature; logical-structural modeling for developing a flash mob; methods for collecting statistical data on the dissemination of information in social networks; method of observing emotional states in children; analysis of activity products (drawings) when performing the developed correction tasks. Results: the predominance of bright colors, holistic images and the absence of pronounced signs of aggressiveness or increased anxiety in children’s works allow us to consider the art therapy flash mob as a stabilizing and resourceful form of creative activity. Quantitative and qualitative indicators of the spread of the flash mob indicate its compliance with the current emotional demand of society and its potential as a tool for primary psychological support for children. Conclusions: art therapy flash mob can be effectively integrated into the practice of psychological assistance, psychoeducation, and educational initiatives as an additional means of prevention and reducing anxiety in children in times of crisis social changes.